The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1088/0031-9155/52/8/016
|View full text |Cite
|
Sign up to set email alerts
|

Patient-specific dosimetry of conventional and intensity modulated radiation therapy using a novel full Monte Carlo phase space reconstruction method from electronic portal images

Abstract: Electronic portal imagers have promising dosimetric applications in external beam radiation therapy. In this study a patient dose computation algorithm based on Monte Carlo (MC) simulations and on portal images is developed and validated. The patient exit fluence from primary photons is obtained from the portal image after correction for scattered radiation. The scattered radiation at the portal imager and the spectral energy distribution of the primary photons are estimated from MC simulations at the treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…38͒ and even by the patient/phantom placed in the beam. 39 A further development for improving MC-based kernel generation is to take the variation of the incident energy spectra into consideration. Kernels are created in terms of the energy spectra of open and blocked MLC fields and depend on the radial distance from the central axis.…”
Section: Introductionmentioning
confidence: 99%
“…38͒ and even by the patient/phantom placed in the beam. 39 A further development for improving MC-based kernel generation is to take the variation of the incident energy spectra into consideration. Kernels are created in terms of the energy spectra of open and blocked MLC fields and depend on the radial distance from the central axis.…”
Section: Introductionmentioning
confidence: 99%
“…The dose calculated within the patient model was then compared to the treatment plan 95,96 . A 3D dose calculation but using comprehensive Monte Carlo simulations has also been reported 97 . Another algorithm requires both non-transit and transit EPID images to determine the transmission through the patient.…”
Section: Transit Dosimetrymentioning
confidence: 99%
“…However an increased interest is nowadays in using EPIDs for dosimetric applications such as: pre-treatment fluence verification for intensity modulated radiation therapy (IMRT) [33][34][35], transit dosimetry [26,28,30], portal dose verification during treatment [6,7,9,14,38] and 3D dose reconstruction [18,22].…”
Section: Introductionmentioning
confidence: 99%
“…Several different EPID systems have been utilized, including scanning liquid ion chambers, CCD-based camera systems and amorphous silicon (a-Si) flat-panel detectors [5,10,14,16,18,22,27,35,38]. The a-Si EPID has shown good characteristics for dosimetric purpose, it has a linear response to dose and dose rate and it is stable with time [15], it can acquire images in real-time at a high frame rate and it was also demonstrated that the a-Si EPID signal can be calibrated in terms of absolute absorbed dose [16].…”
Section: Introductionmentioning
confidence: 99%